Influence of free field variability on linear soil structure interaction (SSI) by indirect integral representation. - Savin, E.
An integral equation for the representation of the response of a structure impinged by an incident wave field including soil structure interaction is proposed. It requires the knowledge of the fundamental solution for the overall soil structure domain when a unit load is applied to the structure. This fundamental solution is obtained by means of a substructuring technique and boundary integral equations using the Green tersors for homogeneous or horizontally stratified soil media. The effects of a non stationary modulated random incident field are addressed in terms of the instantaneous power spectral density of the structural response of interest for a given coherency function of the free field. Several applications of the proposed procedure are presented. The first one considers kinematic interaction of a rigid circular foundation and is used to validate the numerical implementation. The second one considers a complex structure on a stiff stratified soil and the last one considers the pounding effect between two adjacent, identical structures resting on a thin soft soil layer.
Keywords: Dynamic substructuring; Boundary element method; Spectral analysis; Soil structure interaction; Pounding effect